Norway : Financial Sector Assessment Program-Technical Note- Macroprudential Policy. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2015)
This Technical Note reviews macroprudential policy in Norway. The authorities have taken or announced a wide range of macroprudential measures to address systemic risk. Since the 2008 global financial crisis, the authorities have deployed a range of measures to safeguard the financial system in the country. These measures include higher capital requirements, including early adoption and implementation of the European Union capital regulations, additional capital buffers, et cetera These macroprudential measures have focused primarily on building the resilience of banks through higher capital requirements. Good progress has been made on reciprocity agreements to ensure that domestic macroprudential policy measures apply to all banking activities with Norwegian customers.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet